1997
DOI: 10.1021/jm9704309
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Retinoidal Actions by Diazepinylbenzoic Acids. Retinoid Synergists Which Activate the RXR−RAR Heterodimers

Abstract: In human HL-60 promyelocytic leukemia cells, diazepinylbenzoic acid derivatives can exhibit either antagonistic or synergistic effects on the differentiation-inducing activities of natural or synthetic retinoids, the activity depending largely on the nature of the substituents on the diazepine ring. Thus, a benzolog of the retinoid antagonist LE135 (6), 4-(13H-10,11,12,13-tetrahydro-10, 10,13,13,15-pentamethyldinaphtho[2,3-b][1,2-e]diazepin-7-yl) benzoic acid (LE540, 17), exhibits a 1 order of magnitude higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
127
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 60 publications
3
127
2
Order By: Relevance
“…Am80 is a synthetic retinoid that exhibits RAR alpha-selectivity with some RAR beta-binding ability. Although it has been reported that the RAR alpha-binding affinity of Am80 is higher than that of ATRA [27], its inhibitory effect on cell growth observed in this study was lower compared to ATRA. RAR alpha does not seem to be the major RAR subtype for the regulation of cell growth in MCT cells.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Am80 is a synthetic retinoid that exhibits RAR alpha-selectivity with some RAR beta-binding ability. Although it has been reported that the RAR alpha-binding affinity of Am80 is higher than that of ATRA [27], its inhibitory effect on cell growth observed in this study was lower compared to ATRA. RAR alpha does not seem to be the major RAR subtype for the regulation of cell growth in MCT cells.…”
Section: Discussioncontrasting
confidence: 76%
“…ATRA activates only RARs, while 9cRA activates both RARs and RXRs [4,13,16,20]. Am80 can only bind to RAR alpha and beta, though their binding affinities are more potent than ATRA [27].The potential interaction between retinoids and cancer therapy has been recognized for decades, acute promyelocytic leukemia (APL) being the most notable example. APL can be effectively eradicated by retinoids, and therefore forms the prototype for retinoid-based therapies [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate if the enhancement of TRAIL-mediated apoptosis requires retinoid receptor activation, two pan-antagonists, one blocking the RAR receptors (LE540) and the other blocking the RXR receptors (HX531), were tested in the A547 and AD10 cell lines. 36,37 Preincubation with these antagonists did not inhibit the enhancement in TRAIL-mediated apoptosis induced by 4HPR in the cell lines tested (A547 shown in Figure 3b and AD10 not shown). To demonstrate that the inhibitors block RAR-or RXR-mediated effects, we treated the A547 cell line with ATRA plus TRAIL in the presence or absence of both inhibitors.…”
Section: The Combination Of 4hpr and Trail Induces Caspase-mediated Amentioning
confidence: 89%
“…In some experiments, cells were costimulated with t-RA (0.5 -5 M) and H 2 O 2 (150 M). To examine roles of RAR and RXR in the regulation of MKP-1 by retinoids, the following agonists and antagonists were used: RAR agonist TTNPB (0.1-1 M) (24), RXR agonist AGN194204 (1 nM to 1 M) (25), RAR/RXR panagonist 9-cis-RA (1 nM to 10 M), RAR␣ agonist Am580 (0.01 nM to 0.01 M) (26), RAR␤ agonist CD2314 (0.1 nM to 1 M) (27), RAR␥ agonist CD666 (0.1 nM to 1 M) (26), RAR antagonist AGN193109 (0.1-5 M) (24), RXR antagonist HX531 (0.1-5 M) (28,29), RAR␣ antagonist ER50891 (0.1 M) (30), RAR␤ antagonist LE135 (0.1 M) (31,32), and RAR␥ antagonist MM11253 (also known as SR11253; 0.1 M) (33,34). Cells were pretreated with or without 10 -50 times higher concentrations of antagonists for 10 min and then stimulated with agonists for 1 h.…”
Section: Methodsmentioning
confidence: 99%